Mở rộng các phép toán quan hệ cho null phụ thuộc ngữ cảnh - Hiền, Bùi Thị Thúy (Journal of Computer Science and Cybernetics, 2016)
In this paper, we apply the concept of model introduced in [2] to define extended relational algebra operators. It is proved that these extensions have properties which are formally stated as being adequate and precise.